Implementation of Pharmaceutical Care or Hypertension Patients in Communty Health Center of Lubuk Pakamdeli Serdang - Darmirani, Yosi; Dalimunthe, Aminah; Khairunnisa, Khairunnisa (Journal La Medihealtico, 2024)
The objective of this research was to provide pharmaceutical care to patients with Hypertension and assess its effects on the occurrence of drug-related problems (DRPs), clinical outcomes, adherence levels, and quality of life of Hypertension patients at Puskesmas (Community Health Center) Lubuk Pakam. This research used a comparative experimental approach using a prospective cohort study design to assess the effects of an intervention on 73 individuals with Hypertension between March and August 2021. The PCNE V9.00 instrument was used to identify the occurrence of Drug-Related Problems (DRPs). Adherence level data was collected through the MMAS-8 questionnaire. Random blood glucose (RBG) data and Blood Pressure values were obtained by directly examining patients. The EQ-5D-3L questionnaire was used to gather data on the quality of life. The data were analyzed using the Wilcoxon Signed-Rank test and Friedman test in the SPSS V22.0 software. The findings indicated that the average occurrence of drug-related problems (DRPs) before to the intervention was 1.436 ± 0.502, however after the intervention, it decreased to 0.282 ± 0.456 (α <0.05). The mean blood pressure before to the intervention was 278.58 ± 75.278 mmHg, whereas after the intervention it decreased to 179.68 ± 14.008 mmHg (α <0.05). There was a substantial rise in the mean adherence score before to the intervention, from 5.00 ± 0.89 to 8.48 ± 0.77 (α<0.05). Similarly, the average quality of life score increased from 0.878 ± 0.176 to 1 ± 0.09 after the intervention (α<0.05).